Problemy i potrzeby uczniów klas IV szkoły podstawowej w relacjach z rówieśnikami - Deptuła, Maria; Borucka, Anna (Studia Edukacyjne, 2020)
Deptuła Maria, Borucka Anna, Problemy i potrzeby uczniów klas IV szkoły podstawowej w relacjach z rówieśnikami [Problems and Needs of 4th Grade Students in their Relations with Peers]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 57-84. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.4 The aim of the paper is to present the results of longitudinal questionnaire surveys carried out among students of the 4th grade on their problems and needs in relations with peers. Method: Students from 17 classes from all IV grades existing in the 2017/2018 school year in public schools in Bydgoszcz took part in the study. An anonymous questionnaire containing 21 closed-end questions and open questions regarding the relationship with peers and teachers was used. Results: The qualitative analysis was used to distinguish categories of students’ statements, which referred to individual experiences related to (1) functioning among peers and (2) the social climate of the school. Quantitative analyses did not show any correlation between student statements and variables related to the school environment. In contrast, there was a correlation between the frequency of statements about changes in the class and the wishes related to the desirable behavior towards the respondent and the quality of the conditions of psychosocial development in relation with peers.